Reorienting The Resolution of Foreign Investment Disputes Through Domestic Institutional Arbitration Following Indonesia’s Unilateral Termination of The Bilateral Investment Treaty (BIT) - Herlina Diva Pratika; Muhammad Alvin A.T; Naufal Hanif Fakhri W; Nicolas Al Hanafiah; Satriyo Wibowo S; Muhaimin Fachrul F; Radithya Putra Taqwa; Diana Setiawati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Indonesia's gradual termination of numerous Bilateral Investment Treaties since 2014 has generated significant debates concerning the future architecture of foreign investment dispute settlement and the adequacy of domestic legal institutions in replacing conventional Investor State Dispute Settlement mechanisms. This study examines the legal implications of treaty termination for investor protection and evaluates the capacity of domestic institutional arbitration to serve as an alternative forum for resolving foreign investment disputes. Employing a non empirical normative legal research design, the study relies on statutory analysis, conceptual analysis, and comparative legal analysis of Indonesian legislation, investment arbitration jurisprudence, policy documents, and scholarly literature. The findings indicate that the termination of Bilateral Investment Treaties has altered the normative foundation of foreign investment protection by reducing direct access to treaty based arbitration while expanding the importance of domestic legal institutions. Although Indonesia possesses a formal arbitration framework capable of supporting dispute resolution, institutional legitimacy, procedural transparency, arbitrator independence, and international recognition remain critical challenges for the transition from international arbitration to domestic forums. The study further demonstrates that future investment governance requires the establishment of a specialized investment arbitration framework integrating sustainability principles, investor obligations, human rights considerations, and climate justice commitments. A reformed domestic arbitration architecture is essential for balancing regulatory sovereignty, legal certainty, and long term investor confidence within Indonesia's evolving investment regime.